Distinction of Fly Artifacts from Human Blood using Immunodetection1. Issue 6 (21st February 2018) - Rivers, David B.; Acca, Gillian; Fink, Marc; Brogan, Rebecca; Chen, Dorothy; Schoeffield, Andrew
Abstract: Insect stains produced by necrophagous flies are indistinguishable morphologically from human bloodstains. At present, no diagnostic tests exist to overcome this deficiency. As the first step toward developing a chemical test to recognize fly artifacts, polyclonal antisera were generated in rats against three distinct antigenic sequences of fly cathepsin D‐like proteinase, an enzyme that is structurally distinct in cyclorrhaphous Diptera from other animals. The resulting rat antisera bound to artifacts produced by Protophormia terraenovae and synthetic peptides used to generate the polyclonal antisera, but not with any type of mammalian blood tested in immunoassays. Among the three antisera, anti‐md3 serum displayed the highest reactivity for fly stains, demonstrated cross‐reactivity for all synthetic peptides representing antigenic sequences of the mature fly enzyme, and bound artifacts originating from the fly digestive tract. Further work is needed to determine whether the antisera are suitable for non‐laboratory conditions.